PENERAPAN TERAPI KOMPLEMENTER UNTUK MENGURANGI KECEMASAN DAN NYERI PADA AKSEPTOR KB IMPLANT - Widaryanti, Rahayu; Riska, Herliana; Ratnaningsih, Ester; Yuliani, Istri (Universitas Respati Yogyakarta, 2021)
Background: Long-term contraception is the most cost-effective type of modern contraception and to prevent unwanted pregnancies for 3-10 years, one of the methods of MKJP is implant birth control. In 2019, the coverage of long-term contraception acceptors was 23.1%, and the number of implant users was 4.7%. Many acceptors were less interested in implants because they were afraid of how to install them. Therefore, to reduce anxiety and pain, the servants tried to use complementary therapy such as the use of virtual reality, slow deep breathing, and lavender essential oil.Â Methods: This community service activity is included in a series of events commemorating World contraception day and contributes to the success of the 250,000 MKJP programs launched by BKKBN. The activity was carried out on 19 and 24 August 2020 at PMB Istri Yuliani and was attended by 28 implant acceptors.Â Results: The number of implant acceptors who participated in this activity was 28 mothers, with an average age at healthy reproductive age (85.7%), an average level of education for secondary education (85.7%), and having more than 1 child ( 64.3%) only 32.1% of the acceptors have never used family planning before, the rest have used various contraceptive methods. The use of effective complementary therapies can reduce anxiety levels in mothers by 9.50 points. Besides, the use of complementary therapies is also effective in reducing pain felt by implant acceptors.Â Conclusion: Complementary virtual reality therapy, slow deep breathing, and lavender essential oil can reduce the level of anxiety and pain in implant family planning acceptors.Keywords: anxiety, pain, implants, complementary therapy